2007
DOI: 10.1628/093245607781261351
|View full text |Cite
|
Sign up to set email alerts
|

Reference-Dependent Preferences and the Impact of Wage Increases on Job Satisfaction: Theory and Evidence

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 24 publications
(23 reference statements)
6
38
0
3
Order By: Relevance
“…9 See Burchardt (2005), Di Tella, Haisken-De New, and MacCulloch (2010), Grund and Sliwka (2007), Inglehart and Rabier (1986), and Senik (2008).…”
Section: Methodsmentioning
confidence: 99%
“…9 See Burchardt (2005), Di Tella, Haisken-De New, and MacCulloch (2010), Grund and Sliwka (2007), Inglehart and Rabier (1986), and Senik (2008).…”
Section: Methodsmentioning
confidence: 99%
“…A number of empirical analyses have examined whether this hypothesis holds . These studies have found that income changes from the past affect individuals' current happiness even after controlling for current income (Burchardt 2005;Clark 1999;Grund and Sliwka 2007); they also have found that comparisons with the mean income of the studied group also matter for people's happiness (Blanchflower and Oswald 2004;Clark and Oswald 1996;Ferrer-i-Carbonell 2005). …”
Section: Research Questionsmentioning
confidence: 96%
“…He uses a cross section built from the first two waves of the British Household Panel Survey (BHPS) for his study. Grund and Sliwka (2007) state for the German case that job satisfaction is positively related to wage increases for white collar workers in particular.…”
Section: Theoretical Approaches and Previous Empirical Findingsmentioning
confidence: 96%